Bark eaudiobook Stories. - Moore, Lorrie (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2014)
"Fifty years from now, it may well turn out that the work of very few American writers has as much to say about what it means to be alive in our time as that of Lorrie Moore" (Harper's). A literary event—a new collection of stories by one of America's most beloved and admired short story writers, her first collection in fifteen years. In these eight masterful stories, Lorrie Moore, in a perfect blend of craft and bewitched spirit, explores the passage of time and summons up its inevitable sorrows and hilarious pitfalls to reveal her own exquisite, singular wisdom. In "Debarking," a newly divorced man tries to keep his wits about him as the United States prepares to invade Iraq, and against this ominous moment, we see—in all its irresistible hilarity and darkness—the perils of divorce and what can follow in its wake. In "Foes," a political argument goes grotesquely awry as the events of 9/11 unexpectedly manifest at a fund-raising dinner in Georgetown. In "The Juniper Tree," a teacher, visited by the ghost of her recently deceased friend, is forced to sing "The Star-Spangled Banner" in a kind of nightmare reunion. And in "Wings," we watch the unraveling of two once-hopeful musicians who neither held fast to their dreams nor struck out along other paths as Moore deftly depicts the intricacies of dead ends and the workings of regret. Gimlet-eyed social observation, the public and private absurdities of American life, dramatic irony, and enduring half-cracked love wend their way through each of these narratives in a heartrending mash-up of the tragic and the laugh-out-loud—the hallmark of Lorrie Moore–land.